Evidence Linking PPARG Genetic Variants with Periodontitis and Type 2 Diabetes Mellitus in a Brazilian Population - Cirelli, Thamiris [UNESP]; Nicchio, Ingra G. [UNESP]; Bussaneli, Diego G. [UNESP]; Silva, Bárbara R. [UNESP]; Nepomuceno, Rafael [UNESP]; Orrico, Silvana R. P. [UNESP]; Cirelli, Joni A. [UNESP]; Theodoro, Letícia H. [UNESP]; Barros, Silvana P.; Scarel-Caminaga, Raquel M. [UNESP] (My University, 2023)
The peroxisome proliferator-activated receptor gamma (PPARG) gene encodes a transcription factor involved in the regulation of complex metabolic and inflammatory diseases. We investigated whether single nucleotide polymorphisms (SNPs) and haplotypes of the PPARG gene could contribute with susceptibility to develop periodontitis alone or together with type 2 diabetes mellitus (T2DM). Moreover, we evaluated the gene–phenotype association by assessing the subjects’ biochemical and periodontal parameters, and the expression of PPARG and other immune response–related genes. We examined 345 subjects with a healthy periodontium and without T2DM, 349 subjects with moderate or severe periodontitis but without T2DM, and 202 subjects with moderate or severe periodontitis and T2DM. PPARG SNPs rs12495364, rs1801282, rs1373640, and rs1151999 were investigated. Multiple logistic regressions adjusted for age, sex, and smoking status showed that individuals carrying rs1151999-GG had a 64% lower chance of developing periodontitis together with T2DM. The CCGT haplotype increased the risk of developing periodontitis together with T2DM. The rs1151999-GG and rs12495364-TC were associated with reduced risk of obesity, periodontitis, elevated triglycerides, and elevated glycated hemoglobin, but there was no association with gene expression. Polymorphisms of the PPARG gene were associated with developing periodontitis together with T2DM, and with obesity, lipid, glycemic, and periodontal characteristics.
Keywords: dyslipidemias; obesity; periodontitis; peroxisome proliferator-activated receptors; single nucleotide polymorphisms; type 2 diabetes mellitus